Evaluation of the Reliability of Electrocardiographic Criteria for Cardiac Hypertrophy Based on Echocardiographic Data - Augustaitytė, Agnė; Kalinauskienė, Eglė (Acta medica Lituanica, 2022)
Background. Left ventricular hypertrophy (LVH) regardless of other risk factors may be associated with an increased risk of mortality from cardiovascular diseases. Therefore, timely diagnosis for LVH is important in order to avoid possible complications. One of the simplest and cheapest methods to diagnose LVH is electrocardiography (ECG). Although a number of ECG criteria for LVH is known, their reliability varies in many studies. Aim. To evaluate the reliability of ECG criteria for LVH based on transthoracic echocardiography (TTE) data. Methods. The study included all consecutive patients in Kaunas Clinical Hospital Department of Cardiology from December 2019 until March 2020 and from September until October 2020, after applying the inclusion and exclusion criteria. The sensitivity and specificity of the ECG criteria for LVH were assessed based on TTE measurements performed during the same inpatient setting. The reliability of the ECG criteria for LVH was assessed using ROC curves. Reliability differences in gender, age and nutritional status groups were assessed using ANOVA statistical method. Results. Data from 95 patients were analyzed (63.2% were women and 36.8% were men). The sensitivity, specificity and AUC of Sokolow–Lyon criterion were 9.38%, 85.71% and 0.44 (p = 0.034), R in aVL – 6.25%, 90.48% and 0.51 (p = 0.038), Cornell – 21.88%, 100 % and0.69 (p = 0.084), Cornell product – 31.25%, 95.24% and 0.72 (p = 0.070), Peguero–Lo Presti – 31.25%, 85.71% and 0.68 (p = 0.053), respectively. No statistically significant differences were observed among the individual gender, age and nutritional status groups. Conclusions. Sokolow–Lyon and RaVL criteria were not statistically significantly reliable in LVH diagnosis compared to TTE, unlike the Cornell, Cornell product, and Peguero–Lo Presti criteria.